DEVELOPMENT STUDENT WORKSHEET ORIENTED PROBLEM BASED LEARNING TO TRAIN CREATIVE THINKING SKILLS IN CHEMICAL EQUILIBRIUM MATTER (UNESA Journal of Chemical Education, 2016)
The purpose of this research is to know the feasibility of student worksheet with Problem Based Learning oriented to train creative thinking skills, determine student responses and the worksheet role in training student creative thinking skills such as Fluency, Flexibility, Originality in the chemical equilibrium matter. The object of this reasearch is student worksheet oriented Problem Based Learning to train creative thinking skills in chemical equilibrium matter. Collecting data method used questionnaires and tests. The questionnaire method consists review sheets, feasibility sheet, and the student questionnaire responses sheet and the test method used to determine the ability of creative thinking of students through worksheets developed. This researches conducted according to the 4D development procedure. Feasibility validation results were analyzed by quantitative descriptive method, based on a Likert scale. Analysis of student responses using a Gutman Scale and creative thinking skill analyzed by descriptive methode. The experiment result shown that the Chemistry worksheet oriented Problem Based Learning in the chemical equilibrium materials are feasible with the 1st and 2nd worksheet validation result of content, presentation, graphics and linguistic criteria are 91,7%; 88,3%; 91,7% and 79,2%. The students responses to the 1st and 2nd worksheet based on content, presentation, graphics and linguistic criteria are 95,5%; 93,3%; 96,6%; 100% and at 2nd worksheet are 95,5%; 93,3%; 100%; 100%. Developed student worksheet can train students creative thinking skills, it shown by student answer which already reflected the creative thinking activity such as fluency (creative thinking level 1), originality or flexibility (creative thinking level 2), originality or fluency (creative thinking level 3) and, originality and flexibility (creative thinking level 4) in the 1st and 2nd worksheet. Keywords: Student Worksheet, Problem Based Learning, Creative Thinking Skill, Chemical Equilibrium.